A Process Study of the Development of Capabilities for Replication in an Evolving Franchise Chain - Garg, Vinay K.; Goss, Benjamin D.; Rothschild, Philip C. (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The purpose of this paper is to extend insight about processes and routines needed for franchise replication and makes an important contribution to understanding ways through which dynamic capabilities are created. Based on a grounds-up study, this paper utilizes a storyline approach (Miles & Huberman, 1994) to present interview data obtained from interviews with elite informants (IEIs) of the host company and its archival data. Evolution of capabilities, both substantive and dynamic, are captured in the findings section. Of the seventeen interviews, seven subjects were location heads and ten corporate executives. Interviews with corporate executives included questions pertaining to their functional specialty as well. Finally, implications for future research and practice are discussed.